Chapter European Health System Typologies: Last 30 Years Under Review - Isabel Tavares, Aida (InTechOpen, 2017)
The quest of the researcher to classify national health systems into homogeneous groups has a long history. In this paper, the last 30 years are divided in two periods (1985-2000 and 2000-2015) in order to present and briefly describe the most influential national health system typologies.